2020
DOI: 10.3390/s20247231
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Aircraft Touchdown Using Longitudinal Acceleration and Continuous Wavelet Transformation

Abstract: The paper presents a methodology enabling the detection of aircraft touchdowns based on data obtained from accelerometers attached to the structural parts of the airframe in the cockpit or passenger compartment. Precise determination of the moment and place of touchdown of the main landing gear is challenging when analysing parameters such as height, flight speed and rate of descent. During the tests of the I-31T aircraft, it turned out that vibrations of the aircraft structure caused by the contact of the fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The estimation results are presented in the form of time charts (Figure 15A and Figure 16A). The conducted wavelet analysis [31] confirmed the assumptions that the estimation based on Equation (1) would be represented by a slow-varying (LF) signal (Figure 15B), while applying the dependencies of Equation ( 12) would make it possible to obtain an estimate containing components with much higher frequencies (Figure 16B).…”
Section: Frequency Analysis Of Signals Selected For Estimationmentioning
confidence: 55%
“…The estimation results are presented in the form of time charts (Figure 15A and Figure 16A). The conducted wavelet analysis [31] confirmed the assumptions that the estimation based on Equation (1) would be represented by a slow-varying (LF) signal (Figure 15B), while applying the dependencies of Equation ( 12) would make it possible to obtain an estimate containing components with much higher frequencies (Figure 16B).…”
Section: Frequency Analysis Of Signals Selected For Estimationmentioning
confidence: 55%
“…Results show that although the smartphone-based version of the IMUMETER recognizes airplane motion’s phases correctly, the accuracy of distance measurement was insufficient, mainly due to weak accelerometers and GNSS sensor capabilities (acquisition time 1s). It was concluded that a DGPS-based hardware platform with accelerometers of high-frequency response, such as for example used in the cited works [ 27 , 28 , 29 ], would be used in an improved version of the IMUMETER, which is being developed as the next step of this project. Additionally, one practical conclusion is that the use of a smartphone as a hardware platform for airplane motion recognition is rather impossible, as a result of too-slow data acquisition related to airplane motion velocity.…”
Section: Discussionmentioning
confidence: 99%
“…These fields are also propagated from external sources, such as radio navigation systems or communication systems. The issue is of pivotal importance, given the interactions between these fields [5].…”
Section: Introductionmentioning
confidence: 99%